ОСНОВИ МОНІТОРИНГУ В ЕЛЕКТРОЕНЕРГЕТИЦІ. ПРО ПОНЯТТЯ МОНІТОРИНГУ - Стогній, Б.С.; Сопель, М.Ф. (Інститут електродинаміки НАН України, Київ, 2012)
New definition of monitoring concept is given in this article. It differs from known concepts by the fact that except the function of supervision the state estimation function has been added to monitoring process. The necessity of this concept’s introduction is based on the goal of the modern monitoring, the characteristics of its technical realisation and fundamental community of procedures. The base tasks and classification of monitoring process based on a functional attributes is described. Types, base and system procedures, operations of the monitoring system are defined. Their intercommunication is shown. References 8, figures 3.